The Efficacy of Podcast Advertising: Measuring Audience Perception and Behavioral Impact - Akyuz, Biju Ibrahim (Journal of Global Economy, Business and Finance, 2026)
In recent times, podcasts have achieved a huge set of audience and are growing at a great scale. In India, the industry has acquired third place and has brilliant opportunities in the sectors of education, entertainment, technology, news, etc. There is a huge scope in the industry for sure, but it is yet to be explored. Podcasting platforms these days are focused more on advertisement revenue models. The model is best suited for brands who want to promote themselves on different kinds of media. This research paper specifically focuses on podcasting as a medium for advertising and helps us understand whether or not advertisements on podcasts have a visible effect on the minds of the audience.